A utilização do mapa mental como instrumento de apoio na prática pedagógica: impactos nos processos de ensino e de aprendizagem - Sales, Maria Geslane (2024)
This work presents mind maps as methodological instruments developed as an intervention project to be presented for the Professional Master's Degree in Sociology in a National Network. To carry it out, the following specific objectives were established: to analyze the grade point averages of sixteen third-year high school classes in the first three semesters of 2022; to build a didactic sequence; to perceive the impact of the use of mind maps on learning in the Sociology discipline in the third year of 2023; to analyze the grade points of the third-year classes of 2023 based on the application of mind maps as a methodological instrument in Sociology classes, comparing them with the results of the previous year; to analyze the influence of variables involving the social, economic and cultural context that may eventually interact with student learning; to discuss the results of the use of mind maps. This study arises from the need to understand the difficulties that affect student learning in the Sociology discipline. This work is of a qualitative and quantitative nature, carried out through bibliographic and field research. The bibliographic research brings a discussion about the processes that involve teaching practice and the need to develop new methodologies that can contribute to the teaching and learning processes. A brief debate was also held about the variables that make up the social, cultural, and economic context of young people, using both specific bibliographies and data related to the students surveyed. The data were collected from a questionnaire that made it possible to survey the averages of the classes in the first three semesters of 2022, as well as allowing the elaboration of a “portrait” of the classes based on the application of a socioeconomic questionnaire, the same occurring in the 2023 classes that also had the collection applied, consequently resulting in the obtaining of data related to the grades and the context of the students. After obtaining and comparing the data obtained in 2022 and 2023, it was possible to identify the positive impacts of mind maps on class averages, since in 2022 the majority had an average below 6 and in 2023 this was reversed, with only one class appearing with an average below the average of 6, which is the average established by the educational institution.